Cost-effectiveness of cardiovascular risk assessment and management among adults with hypertension in China: A modelling study - Siqi Lin; Liming Lin; Wenyao Peng; Xuan Liu; Xi Li; Jiapeng Lu; Shouling Wu (American Journal of Preventive Cardiology)
Objective: Blood pressure reduction alone is insufficient for significant cardiovascular risk improvement in patients with hypertension. Cardiovascular risk assessment and management are recommended to prevent and control cardiovascular diseases (CVD), but their cost-effectiveness in real-world Chinese settings is unclear. This study evaluated the benefits and cost-effectiveness of two strategies based on cardiovascular risk in Chinese hypertensive patients aged ≥35 years: statin treatment and lifestyle management + statin treatment. Methods: A decision-analytic Markov cohort model was constructed to estimate health benefits and incremental cost-effectiveness ratios between two interventions and no intervention over 10-year and lifetime horizons. Parameters including stroke/myocardial infarction (MI) incidence, all-cause mortality, costs, and health utilities were extracted from the Kailuan study, published literature, or public datasets. Sensitivity analyses assessed the influence of parameter uncertainty on the results of base-case analysis. Results: Statin treatment alone in hypertensive patients with high cardiovascular risk was projected to avert 847,350 stroke cases, 1412,250 MI cases and 564,900 all-cause deaths over a 10-year time horizon. Lifestyle management combined with statin treatment could prevent more cardiovascular and death events and was highly cost-effective ($1219.76/quality-adjusted life-year vs. gross domestic product per capita $12,680.83). Over a lifetime horizon, it was highly cost-effective regardless of the age when the combined intervention was started, with earlier initiation yielding greater benefits in preventing cardiovascular events. Sensitivity analyses confirmed robust results. Conclusion: Cardiovascular risk assessment and combined management in hypertensive individuals aged ≥35 years would generate substantial health gains and represent a highly cost-effective CVD prevention strategy in China.